Understanding Components of Duration of Untreated Psychosis and Relevance for Early Intervention Services in the Canadian Context: Comprendre les Composantes de la Durée de la Psychose Non Traitée et la Pertinence de Services D'intervention Précoce Dans le Contexte Canadien. (October 2021) - Malla, Ashok; Dama, Manish; Iyer, Srividya; Joober, Ridha; Schmitz, Norbert; Shah, Jai; Issaoui Mansour, Bilal; Lepage, Martin; Norman, Ross
Background: Clinical, functional, and cost-effectiveness outcomes from early intervention services (EIS) for psychosis are significantly associated with the duration of untreated psychosis (DUP) for the patients they serve. However, most EIS patients continue to report long DUP, while a reduction of DUP may improve outcomes. An understanding of different components of DUP and the factors associated with them may assist in targeting interventions toward specific sources of DUP. Objectives: To examine the components of DUP and their respective determinants in order to inform strategies for reducing delay in treatment in the context of an EIS. Methods: Help-seeking (DUP-H), Referral (DUP-R), and Administrative (DUP-A) components of DUP, pathways to care, and patient characteristics were assessed in first episode psychosis ( N = 532) patients entering an EIS that focuses on systemic interventions to promote rapid access. Determinants of each component were identified in the present sample using multivariate analyses. Results: DUP-H (mean 25.64 ± 59.00) was longer than DUP-R (mean = 14.95 ± 45.67) and DUP-A (mean 1.48 ± 2.55). Multivariate analyses showed that DUP-H is modestly influenced by patient characteristics (diagnosis and premorbid adjustment; R 2 = 0.12) and DUP-R by a combination of personal characteristics (age of onset and education) and systemic factors (first health services contact and final source of referral; R 2 = 0.21). Comorbid substance abuse and referral from hospital emergency services have a modest influence on DUP-A ( R 2 = 0.08). Patients with health care contact prior to onset of psychosis had a shorter DUP-H and DUP-R than those whose first contact was after psychosis onset (F(1, 498) = 4.85, P < 0.03 and F(1, 492) = 3.34, P < 0.07). Conclusions: Although much of the variance in DUP is unexplained, especially for help-seeking component, the systemic portion of DUP may be partially determined by relatively malleable factors. Interventions directed at altering pathways to care and promote rapid access may be important targets for reducing DUP. Simplifying administrative procedures may further assist in reducing DUP.